2003
DOI: 10.1038/sj.bmt.1704216
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose short-course intravenous ganciclovir as pre-emptive therapy for CMV viremia post allo-PBSC transplantation

Abstract: Summary:In contrast to allogeneic bone marrow transplantation (allo-BMT), there is a paucity of data on cytomegalovirus (CMV) infection and pre-emptive therapy (PT) strategies following allogeneic peripheral blood stem cell (allo-PBSC) transplantation. We report here on the patterns of CMV infection in a cohort of 225 patients following sibling donor allo-PBSC transplantation. In an attempt to reduce neutropenia, we used intravenous low-dose shortcourse (LDSC) ganciclovir (GCV) 5 mg/kg once daily for 21 days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…15 The incidence of neutropenia was also low in the present cohort of patients as well. One patient required a treatment change to foscarnet and one patient required growth factor support secondary to declining ANC related to GCV.…”
Section: Tablementioning
confidence: 71%
See 2 more Smart Citations
“…15 The incidence of neutropenia was also low in the present cohort of patients as well. One patient required a treatment change to foscarnet and one patient required growth factor support secondary to declining ANC related to GCV.…”
Section: Tablementioning
confidence: 71%
“…15 In the current series, we delayed the initiation of ODG until a threshold CMV load of X10 000 copies/ml whole blood in 28 clinically stable patients. Ten of these patients (36%) required a dose increase to GCV 5 mg/kg twice daily for increasing viral loads.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Favorable outcomes of preemptive therapy with GCV 5 mg/kg once daily for BMT and PBSCT recipients were previously reported. [5][6][7] In previous studies, dose-escalation of GCV or a change to foscarnet therapy was required in 32-39% patients when the initial response was not sufficient. Recurrence of CMV infection after the completion of initial preemptive therapy was observed in 33-43% patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 In an attempt to reduce the incidence of GCV-related neutropenia, preemptive therapy with GCV 5 mg/kg once daily has previously been used as initial induction therapy for BMT and peripheral blood SCT (PBSCT) recipients. [5][6][7] The favorable outcomes suggested that this strategy could reduce the incidence of GCV-related neutropenia but retained the efficacy for preventing CMV disease in BMT and PBSCT recipients.…”
Section: Introductionmentioning
confidence: 99%